Drug Addiction Students and Heart Rate Variability Biofeedback: A Study on Solat Effect - Salam, Urme; Muhammad Nubli, Abdul Wahab (WSEAS Press, 2013)

(untitled)
Nowadays, addiction is a common problem of all over the world and its severity is increasing day by day. The most alarming fact is that addiction is going to be famed among youths. To address this social disease heart rate variability biofeedback (HRV BFB) may be one of the simple approaches, which analyzes the joint time/frequency of the beat-to-beat changes in the heart rate or rise and fall of heart rate. HRV BFB is used as a tool for self-regulating physiological conditions to improve the psycho physiological interfaces. On the other hand, Salah is a very significant Islamic repentance to the Muslim. Consequently, it has an extraordinary power to decrease effectively the anxiety and stress from the mind of human being. In addition, it can be used as the therapeutic agents in several cases. In this work, authors selected 17 male students among 23 students from secondary school, Malaysia and they were treated with Salah as a psychophysiological stimulant, through heart rate variability (HRV) which was an objective method to realize the changes of emotional response . The results of this study indicated that the effect of Salah and HRV BFB improved the physiological conditions and a significant correlation was also observed between the Salah and BFB, which is necessary to intervene the addiction.